Pengaruh Pemberian Ekstrak Ikan Gabus terhadap Kadar Albumin dan Lama Penyembuhan Ruptur Perineum Derajat II pada ibu Nifas Primipara - Nunung Erviany; Ummul Khair; Hasnia Hasnia; Titin Fatimah (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2024)
Introduction: Proteins are an important part of the human immune system. They play a role in a variety of functions related to immunity, including as structural components for immune cells, such as antibodies (which are a type of protein) and white blood cells. Objective: This study aims to determine the effects of Moringa leaf extract for 10 days to albumin and primiparous puerperal women with ruptured perineum degree II in the district Soppeng. Metodes: Design research is a quasi-scale experiment using two groups, intervention and control groups. The sample set, that primiparous puerperal women with ruptured perineum stage II of 50 respondents. The sampling technique is done purposively. Results: showed unpaired t test analysis on levels of albumin found the mean pre-intervention 3:09 / 0:30, post intervention 3.75 / 0:55. With the test results are not berpsangan t p value = 0.000 which means no significant effects of extract of catfish in primiparous puerperal women with ruptured perineum degree II. . With unpaired T test results found the value of p = 0.000, which means there is a significant effect of the extract catfish on primiparous puerperal women with ruptured perineum degree II In other words, the extract cork fish provide a positive and significant effect on levels of albumin